The LOGSE in Spanish education. A brief account of a historic change - Marchesi, Álvaro (Avances en Supervisión Educativa, 2020)
The article describes the antecedents that guided the preparation and approval of the General Law of Educational System (LOGSE). The experimental programs and debates prior to the presentation of the White Paper and the LOGSE are analyzed and their objectives, their development and the first years of application are highlighted. The last sections summarize the main strengths and weaknesses of the law.
Keywords: LOGSE; education; educational system